Periodontal status in patients with Alzheimer’s disease: a scoping review - Kartika Indah Sari; Restu Amelia Fauziah; Erli Sarilita; Paulus Anam Ong; Ambrosius Purba; Sunardhi Widyaputra (Majalah Kedokteran Gigi Indonesia, 2022)
Periodontitis is the most common condition of chronic periodontal infection and inflammation in the elderly population. Periodontal disease can cause local inflammation that contributes to higher risk of systemic inflammatory disease. Current research suggests a possible link between periodontal disease and neurodegenerative disease, such as Alzheimer’s disease. The aim of the study is to provide a profile of the periodontal tissue status in people with Alzheimer’s disease. This scoping review followed Joanna Briggs Institute (JBI) guideline, and the searching was conducted using PubMed, Cochrane, and EBSCOHost databases during February 6th – February 7th, 2021 with keywords of periodontal disease, periodontitis, periodontal inflammation, Alzheimer’s disease and dementia. It also included MeSH terms of “periodontal disease” and “Alzheimer’s disease” if available. Additionally, snowballing technique was used to include more articles. The identification and writing process for this article followed the PRISMA-ScR framework. There were 60 articles included in this study. This scoping review shows a profile of general characteristics including decreased oral hygiene and periodontal tissue status showed by high score of plaque and calculus, gingival inflammation, high percentage of Clinical Attachment Loss (CAL), Bleeding on Probing (BOP) along with deterioration of cognitive function. There was a decreasing level of periodontal health along with the decline in cognitive function experienced by AD participants. However, further research is needed to see the mechanism of this relationship.